HERMENEUTICAL THOUGHT OF MUHAMMAD ARKOUN:: INTERPRETING THE QUR'AN IN THE MIDDLE OF CHANGING TIMES - Batubara, Muhammad Fauzi; Ramadhania, Nada; Nasyah, Rahmaifa (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study explores Muhammad Arkoun’s hermeneutical thought in interpreting the Qur’an as an open discourse that should be read critically and contextually. The research is based on the need for a renewed interpretive method that aligns with modern scientific developments and contemporary socio-cultural dynamics. The purpose is to analyze Arkoun’s methodological approach, which integrates social sciences such as linguistics, anthropology, and history in Qur’anic exegesis. This study employs a qualitative library research method, focusing on primary and secondary sources related to Arkoun’s thought. The findings reveal that Arkoun rejects a literalist approach to the text and emphasizes the need to understand revelation within its complex historical and cultural contexts. He introduces concepts such as la mafkûr fîh to uncover unexplored meanings in religious discourse. The study concludes that Arkoun’s approach offers an inclusive, dynamic, and contextually relevant alternative reading of the Qur’an. Its major contribution lies in opening new horizons for Qur’anic Interpretation in the contemporary era.